An integrated analysis of bulk and single-cell sequencing data reveals that EMP1+/COL3A1+ fibroblasts contribute to the bone metastasis process in breast, prostate, and renal cancers - Du, Haoyuan; Wang, Hua; Luo, Yuwei; Jiao, Yang; Wu, Jiajun; Dong, Shaowei; Du, Dong (Frontiers in Immunology, 2023)
Introduction Bone metastasis (BoM) occurs when cancer cells spread from their primary sites to a bone. Currently, the mechanism underlying this metastasis process remains unclear. Methods In this project, through an integrated analysis of bulk-sequencing and single-cell RNA transcriptomic data, we explored the BoM-related features in tumor microenvironments of different tumors. Results We first identified 34 up-regulated genes during the BoM process in breast cancer, and further explored their expression status among different components in the tumor microenvironment (TME) of BoM samples. Enriched EMP1+ fibroblasts were found in BoM samples, and a COL3A1-ADGRG1 communication between these fibroblasts and cancer cells was identified which might facilitate the BoM process. Moreover, a significant correlation between EMP1 and COL3A1 was identified in these fibroblasts, confirming the potential connection of these genes during the BoM process. Furthermore, the existence of these EMP1+/COL3A1+ fibroblasts was also verified in prostate cancer and renal cancer BoM samples, suggesting the importance of these fibroblasts from a pan-cancer perspective. Discussion This study is the first attempt to investigate the relationship between fibroblasts and BoM process across multi-tumor TMEs. Our findings contribute another perspective in the exploration of BoM mechanism while providing some potential targets for future treatments of tumor metastasis.